Yttrium‐90 microsphere radioembolisation for unresectable hepatocellular carcinoma - Abdel‐Rahman, Omar (Cochrane Database Syst Rev, 2020)
BACKGROUND: Hepatocellular carcinoma is the most common liver neoplasm and the sixth most common cancer worldwide. Its incidence has increased dramatically since the mid‐2000s. Although surgical resection and liver transplantation are the main curative treatments, only about 20% of people with early hepatocellular carcinoma may benefit from these interventions. Treatment options for unresectable hepatocellular carcinoma include ablative and transarterial interventions ‐ selective yttrium‐90 microsphere transarterial radioembolisation ‐ in addition to the drug sorafenib. OBJECTIVES: To determine the benefits and harms of yttrium‐90 (Y‐90) microsphere transarterial radioembolisation given as monotherapy or in combination with other systemic or locoregional interventions versus placebo, no treatment, or other similar systemic or locoregional interventions for people with unresectable hepatocellular carcinoma. SEARCH METHODS: We performed electronic searches in the Cochrane Hepato‐Biliary Group (CHBG) Controlled Trials Register, CENTRAL, MEDLINE, Embase, Latin American Caribbean Health Sciences Literature (LILACS), Science Citation Index ‐ Expanded, and Conference Proceedings Citation Index – Science until September 2019. We manually checked the reference lists of primary studies and review articles. SELECTION CRITERIA: We searched for randomised clinical trials. DATA COLLECTION AND ANALYSIS: We used standard Cochrane methods. We extracted information on participants, interventions, outcomes, trial design, and trial methods. We assessed risk of bias of the included trials using pre‐defined domains and the certainty of evidence using GRADE. Our primary review outcomes were all‐cause mortality, quality of life, and serious adverse events; our secondary outcomes were cancer‐related mortality, time to progression of the tumour, tumour response, non‐serious adverse events, and liver transplantation. For dichotomous variables, we calculated risk ratio (RR), and for continuous variables, we planned to calculate mean difference (MD) or standardised mean difference (SMD), with 95% confidence intervals (CIs). We based time‐to‐event data analyses on hazard ratios (HRs). MAIN RESULTS: Six randomised trials with 1340 participants in total fulfilled the review inclusion criteria and provided data for one or more of our analysed outcomes. All trials were at high risk of bias. We assessed the certainty of evidence as low to very low. One trial compared radioembolisation plus sorafenib versus sorafenib alone in people with advanced hepatocellular carcinoma. All‐cause mortality, health‐related quality of life, cancer‐related mortality, time to progression, and tumour response rates were not reported. Serious adverse events were reported in 63 trial participants (39.6%) in the radioembolisation plus sorafenib group versus 70 trial participants (38.5%) in the sorafenib group (very low‐certainty evidence). Hyperbilirubinaemia was approximately three times more common in the radioembolisation plus sorafenib group versus the sorafenib group (14.5% versus 4.4%; very low‐certainty evidence). Fatigue was more common in the radioembolisation plus sorafenib group than in the sorafenib group, at 35.2% versus 24.2% of trial participants.    Two trials compared radioembolisation versus sorafenib for unresectable hepatocellular carcinoma in people with locally advanced hepatocellular carcinoma. From the data we could extract, one‐year all‐cause mortality was 62.7% in the radioembolisation group versus 53.0% in the sorafenib group (1 trial; n = 360; very low‐certainty evidence). There were no differences in the quality of life between radioembolisation and sorafenib groups (1 trial). Global health status subscore was better in the radioembolisation group than in the sorafenib group (P = 0.0048; 1 trial). Fewer participants had serious adverse events in the radioembolisation group than in the sorafenib group (27 (20.8%) in the radioembolisation group versus 57 (35.2%) in the sorafenib group; 1 trial). Median time to progression of the tumour in the radioembolisation group was 6.1 months versus 5.4 months in the sorafenib group (1 trial). The RR for disease control rate was 0.94 (95% CI 0.84 to 1.05; n = 748; 2 trials; very low‐certainty evidence), favouring neither radioembolisation nor sorafenib. In two trials with 734 participants, radioembolisation seemed to be less likely to be associated with hand‐foot skin reaction (RR 0.02, 95% CI 0.00 to 0.06; P < 0.001; low‐certainty evidence), skin rash (RR 0.11, 95% CI 0.04 to 0.34; low‐certainty evidence), diarrhoea (RR 0.11, 95% CI 0.04 to 0.34; low‐certainty evidence), and hypertension (RR 0.10, 95% CI 0.01 to 0.88; low‐certainty evidence). No trial reported cancer‐related mortality.    Three trials compared radioembolisation versus chemoembolisation in people with intermediate‐stage hepatocellular carcinoma. From the data we could extract, none of these trials reported all‐cause mortality and cancer‐related mortality. The RR for serious adverse events was 1.41 (95% CI 0.63 to 3.14; n = 97; very low‐certainty evidence), favouring neither radioembolisation nor chemoembolisation. One trial reported quality of life and noted no differences between intervention groups with regard to this outcome at week 12 (very low‐certainty evidence). Median time to progression was not reached in the radioembolisation group and was 6.8 months in the chemoembolisation group (HR 0.122, 95% CI 0.027 to 0.557; 1 trial). Median time to progression of the tumour in the radioembolisation group was 371 days versus 336 days in the chemoembolisation group (P = 0.5764; 1 trial). Disease control rates (complete response + partial response + stable disease) were 73.3% with radioembolisation versus 76.9% with chemoembolisation (1 trial). According to World Health Organization (WHO) criteria, tumour response was reported in 52% of participants who received radioembolisation versus 63% of those who received chemoembolisation (1 trial). Patients in the chemoembolisation group experienced diarrhoea (P = 0.031; 1 trial) and hypoalbuminaemia (P < 0.001; 1 trial) more frequently. Four trials were sponsored by industry, and two by University. We found two ongoing trials. AUTHORS' CONCLUSIONS: Evidence showing effects of radioembolisation with or without sorafenib compared with sorafenib alone in people with unresectable hepatocellular carcinoma is highly insufficient. We cannot determine if radioembolisation plus sorafenib compared with sorafenib alone affects all‐cause mortality or the occurrence of adverse events. Radioembolisation compared with sorafenib seemed to achieve equivalent survival and to cause fewer adverse effects, but our certainty was very low. Evidence showing effects of radioembolisation versus chemoembolisation in people with unresectable hepatocellular carcinoma is also highly insufficient. Radioembolisation did not seem to differ from chemoembolisation in terms of serious adverse events and quality of life, but the certainty of evidence was very low. Further high‐quality placebo‐controlled randomised clinical trials are needed to assess patient‐centred outcomes.